2002
DOI: 10.1152/ajpregu.00548.2001
|View full text |Cite
|
Sign up to set email alerts
|

Early osmoregulatory stimulation of neurohypophyseal hormone secretion and thirst after gastric NaCl loads

Abstract: Cerebral osmoreceptors mediate thirst and neurohypophyseal secretion stimulated by increases in the effective osmolality of plasma (P(osmol)). The present experiments determined whether an intragastric load of hypertonic saline (ig HS; 0.5 M NaCl, 4 ml) would potentiate these responses before induced increases in P(osmol) in the general circulation could be detected by cerebral osmoreceptors. Adult rats deprived of water overnight and then given intragastric HS consumed much more water in 15-30 min than rats g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…It is important to point out that there was a positive relationship between the number of OT-activated cells and the volume of hypertonic saline consumed, since the animals stimulated to drink, like the PD-2% group, had the greatest number of Fos-OT-ir cells. In accord with these results, there is evidence that intragastric hypertonic infusion enhances OT plasma levels and oxytocin mRNA expression in the hypothalamic nuclei in euhydrated and dehydrated rats, although this peptide does not increase after isotonic intragastric infusion, perhaps because it does not cause substantial hypernatremia or a hypertonic state (20,36,52). Together, these studies suggest that the OT system is a hypertonicity marker; thus the OT circuit may be signaling the entry to the body of a hypertonic sodium solution during sodium access, since 2% NaCl loading or ingestion increases OT neuron activity and OT plasma levels.…”
Section: Effect Of Induced Isotonic Vs Hypertonic Sodium Intake On Pmentioning
confidence: 64%
See 1 more Smart Citation
“…It is important to point out that there was a positive relationship between the number of OT-activated cells and the volume of hypertonic saline consumed, since the animals stimulated to drink, like the PD-2% group, had the greatest number of Fos-OT-ir cells. In accord with these results, there is evidence that intragastric hypertonic infusion enhances OT plasma levels and oxytocin mRNA expression in the hypothalamic nuclei in euhydrated and dehydrated rats, although this peptide does not increase after isotonic intragastric infusion, perhaps because it does not cause substantial hypernatremia or a hypertonic state (20,36,52). Together, these studies suggest that the OT system is a hypertonicity marker; thus the OT circuit may be signaling the entry to the body of a hypertonic sodium solution during sodium access, since 2% NaCl loading or ingestion increases OT neuron activity and OT plasma levels.…”
Section: Effect Of Induced Isotonic Vs Hypertonic Sodium Intake On Pmentioning
confidence: 64%
“…We also studied the neural activity of other brain nuclei previously involved in sodium appetite regulation after PD-induced isotonic or hypertonic NaCl intake and OT plasma levels following the same paradigm, since OT plasma release in other models has been associated with hypernatremic, hyperosmolalic, and hypovolemic stimulation (20,25,52,55).…”
mentioning
confidence: 99%
“…One possible explanation for these studies might be that plasma AVP and Na levels might vary quickly, making it difficult to detect changes. In addition to the central action, it might also be possible that ingested Na stimulated AVP release as well as the sense of thirst through osmoreceptors located in the peripheral tissues (7,27,42). In contrast to the wild-type mice, urine AVP was increased in the 2.0% Na diet group compared with the 0.2% Na group only for 2 mo in the FNDI mice.…”
Section: Discussionmentioning
confidence: 99%
“…In the first experiment, we administered desmopressin (dDAVP), a longacting analog of AVP (13), to the FNDI mouse model to decrease AVP synthesis, and examined possible changes in the phenotype. In the second experiment, we examined whether the excess in Na intake might accelerate the phenotype in the FNDI mice model, as it was demonstrated that the Na intake stimulated AVP release (12,42).…”
mentioning
confidence: 99%
“…Typically as P osm increases, plasma arginine vasopressin and thirst increase. This relationship has been illustrated in numerous studies (Greenleaf 1992;O'Brien et al 1998;Phillips et al 1985;Stricker et al 2002;Thompson et al 1986). However, changes in central volume have been shown to alter this relationship between thirst and P osm .…”
Section: Discussionmentioning
confidence: 77%